Effects of residual strain on magnetoresistance in heterostructures of La0.9Ca0.1MnO3/0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3. (January 2017) - Qi, Yaping; Wang, Lin; Jiang, Yucheng; Wu, Zhenping; Wang, Linjun; Gao, Ju
Abstract: Epitaxial thin films of La0.9 Ca0.1 MnO3 were grown on (100) oriented 0.7Pb(Mg1/3 Nb2/3 )O3 -0.3PbTiO3 (PMN-PT) single-crystal substrates by pulsed laser deposition. The heterostructure composed of manganite and ferroelectric would enable us to control and study the electric/magnetic properties of manganite by means of tunable strain induced via the piezoelectric effect of PMN-PT. X-ray diffraction revealed that the ferroelectric poling remarkably modify the in-plane tensile strain introduced in the La0.9 Ca0.1 MnO3 film, which gives rise to tune resistance and Curie temperature T C . It is also found that due to poling of PMN-PT the magnetoresistance of La0.9 Ca0.1 MnO3 is reduced in the paramagnetic state, but increased in ferromagnetic state. The observed effects of residual strain on magnetoresistance could be explained by the Jahn-Teller distortion and polarization effect on the coexistence of multiple phases. Highlights: Epitaxial thin films of La0.9 Ca0.1 MnO3 were grew on (100) orientedPMN-PT single-crystal substrates. The ferroelectric poling induces decreased in-plane tensile strain in the La0.9 Ca0.1 MnO3 film. The lattice strain significantly affected the magnetoresistance of La0.9 Ca0.1 MnO3 .